Randomized Phase II Trial of Nivolumab With Stereotactic Body Radiotherapy Versus Nivolumab Alone in Metastatic Head and Neck Squamous Cell Carcinoma. Issue 1 (1st January 2021) - McBride, Sean; Sherman, Eric; Tsai, C. Jillian; Baxi, Shrujal; Aghalar, Jahan; Eng, Juliana; Zhi, Wanqing Iris; McFarland, Daniel; Michel, Loren Scott; Young, Robert; Lefkowitz, Robert; Spielsinger, Daniel; et al.
Abstract : PURPOSE: The objective response rate (ORR) for single-agent anti–programmed death receptor 1 (anti–PD-1) therapy is modest in patients with metastatic or recurrent head and neck squamous cell carcinoma (HNSCC). We aimed to test whether radiotherapy may act synergistically with anti–PD-1 therapy to improve response through the abscopal effect. PATIENTS AND METHODS: We conducted a single-center, randomized, phase II trial of nivolumab (anti–PD-1 therapy) versus nivolumab plus stereotactic body radiotherapy (SBRT) in patients with metastatic HNSCC. Patients had at least two metastatic lesions: one that could be safely irradiated and one measurable by RECIST version 1.1. Patients were randomly assigned (1:1), stratified by human papillomavirus status, to nivolumab (3 mg/kg intravenously every 2 weeks) or nivolumab (same dose) plus SBRT (9 Gy × 3) to 1 lesion. The primary end point was ORR in nonirradiated lesions, which was assessed by RECIST in patients with at least one available set of on-treatment images; safety was assessed in a per-protocol population. RESULTS: Between March 11, 2016, and June 22, 2018, 62 patients were randomly assigned to nivolumab (n = 30) or nivolumab plus SBRT (n = 32). There was no statistically significant ORR difference between arms (34.5% [95% CI, 19.9% to 52.7%] v 29.0% [95% CI, 16.1% to 46.6%]; P = .86). There was no significant difference in overall survival ( P = .75), progression-free survival ( P = .79), or response duration ( P = .26). Grade 3-5 toxicities were similar (13.3% v 9.7%; P = .70). CONCLUSION: We found no improvement in response and no evidence of an abscopal effect with the addition of SBRT to nivolumab in unselected patients with metastatic HNSCC.